(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Objective: To study the role of internal podalic version (IVP) in the management of transverse lie with fetal demise in labour and to assess the success and outcome of this almost obsolete procedure in obstetrics. Materials and Methods: Quasi experimental study was done in Shaheed Ziaur Rahman Medical College and Mohammad Ali Hospital, Bogra from January 2001 to December 2006. Results: Within this period total 180 cases transverse lie with intrauterine fetal death (IUFD) were studed. All these case were undiagnosed transverse lie with IUFD in labour and admitted in the hospital through the emergency department. In 60 cases IPV and in 120 cases lower uterine segment caesarean section (LUCS) were done to deliver the dead for per operative and post operative blood transfusion were only 03.33% in cases where IVP was done, and 41.66% in those who under went LUCS (P<.001). Hospital stay in IVP group was only 1.3 days where as 10 days for those who under went LUCS (P<.001). Regarding complications it was almost same in both groups. IVP was also very cost effective required some of taka 300 only where as for LUCS it required about 3000 taka. Conclusion: The success rate of IVP is good. It is cost effective, preserve the future fertility and prevent DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21030 J Bangladesh Coll Phys Surg 2014; 32: 16-20